Standarisasi Wajah Melalui Tren Tiktok Beauty dan Implikasinya pada Teknik Makeup - Anik Maghfiroh; Itsnayni Itsnayni; Marselia Dewi Anggraeni; Varisa Berliana Al-Azhar; Nadine Fahira; Safiyyah Raihana (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The development of social media, particularly TikTok, has played a significant role in shaping beauty trends and constructing ideal facial standards among young generations. The TikTok Beauty phenomenon not only provides diverse makeup references but also reinforces specific visual representations that influence perceptions of beauty. This study aims to examine the relationship between the TikTok Beauty phenomenon, the process of facial standardization, and its implications for the development of makeup techniques. A qualitative approach was employed through content analysis and literature review. Primary data were obtained from observations of popular TikTok videos under the hashtags #beautytrend, #makeup, and #tiktokbeauty, while secondary data were drawn from scholarly literature on beauty standards, social construction, and social media algorithms. The findings indicate that TikTok strengthens certain beauty standards such as fair skin, slim facial contours, and a flawless appearance which in turn influence techniques like complexion layering and visual manipulation. However, the platform also provides space for more inclusive and diverse beauty narratives. This study recommends enhancing aesthetic literacy to ensure that makeup practices prioritize diversity and the unique characteristics of each individual.